ReGTime - Rent Gigaflops someTimes - Dreier, Bernd; Huber, Annja; Karl, Holger; Ungerer, Theo; Zahn, Markus (Trends in Distributed Systems: CORBA and Beyond, International Workshop TreDS '96, Aachen, Germany, October 1-2, 1996, Proceedings)

The Spectator as Participant: The Role of Integrating Audience Laughter in Samuel Beckett's Drama - Tönnies, Merle (Forum Modernes Theater)

Adsorption of group-V elements on III–V (1 1 0) surfaces - Schmidt, W (Surface Science Reports)

3d core-level shifts at - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Surface Science)

Dimerized, buckled, or ideal chains on the diamond (111)2 × 1 surface? - Schmidt, Wolf Gero; Scholze, A.; Bechstedt, F. (Surface Science)

Czermak, Johannes (Hg.), Philosophy of Mathematics. Proceedings of the 15th International Wittgenstein-Symposium, 16–23 August 1992, Kirchberg am Wechsel, Austria, Part 1, Hölder-Pichler-Tempsky: Wien 1993 (= Schriftenreihe der Wittgenstein-Gesellschaft; 20/I) [Zbl. 0836.00022] - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

MacLane, Saunders, “The Protean Character of Mathematics”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [ Zbl 0839.00019], 1–13 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Erwerbssituation, mentale Repräsentation und sprachliche Lokalisationen - Blickpunktinformation als Bestandteil der Raumrepräsentation - Buhl, Heike M. (Sprache und Kognition)
Explored the question of point of view as a part of the mental representation of space. Human Ss: 80 normal German adults (university students) (Exp 1). 48 normal German adults (university students) (Exp 2). Ss participated in 2 separate experiments in which spatial expressions were taken to indicate the point of view in mental representation and in which one object was localized within a route direction context. Results were discussed as to whether working memory load offers an explanation for the availability of viewpoint oriented information that allows for changes in mentally represented point of views.

Forumsbeitrag: Bericht über das Münchner Graduiertenkolleg Geschlechterdifferenz und Literatur - Öhlschläger, Claudia (Der Deutschunterricht 1/1996: Differenzen - diesseits und jenseits von Geschlechterfixierungen (Hg.) Eva Kublitz-Kramer und Eva Neuland)

Chirped fiber Bragg gratings for optical dispersion compensation: How to improve their fabrication accuracy - Sandel, D; Noé, Reinhold (22ND EUROPEAN CONFERENCE ON OPTICAL COMMUNICATIONS, PROCEEDINGS, VOLS 1-6: CO-LOCATED WITH: 2ND EUROPEAN EXHIBITION ON OPTICAL COMMUNICATION - EEOC ‘96)

Analyses of Sub 1/4-Micron MOS-Transistors by Visible Light Emission - Muller, J.; Wirth, G.; Hilleringmann, Ulrich; Goser, K. (ESSDERC ’96: Proceedings of the 26th European Solid State Device Research Conference)

On the Observability of dynamic localization in semiconductor superlattices using optical spectroscopy - Meier, Torsten; Rossi, F.; Je, K.-C; Hader, J.; Thomas, P.; Koch, S.W. (Hot Carriers in Semiconductors)
During the last decade, a variety of field-induced coherent phenomena in semiconductor superlattices has received considerable attention both from a theoretical and from an experimental point of view. For the case of a static applied electric field, the existence of Bloch oscillations has been predicted theoretically and confirmed by means of different experimental techniques of nonlinear optical spectroscopy.

Field-induced exciton ionization studied by four-wave mixing - Meier, Torsten; Koch, M.; von Plessen, G.; Feldmann, J.; Koch, S.W.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Hot Carriers in Semiconductors)
The dynamics of carriers induced by electric fields in semiconductor superlattices has received much interest in recent years. Phenomena like Bloch oscillations and negative differential velocity in these structures have been studied using a variety of experimental techniques [1–5]. One particular point of interest has been the transition of the miniband regime to the Bloch oscillation regime with increasing electric field [6,7]. Cw spectra of strongly-coupled superlattices have evidenced that this transition is concomitant with a rapid field-induced ionization of the zero-field miniband exciton [5,8]. While it has been pointed out from the theoretical side that the field-induced ionization process strongly influences the coherent dynamics in the transition region [9], no systematic experimental investigation of the ionization process has been carried out so far. One interesting question that such an investigation could help to answer is to what extent this ionization process differs from the well-documented case of field-induced exciton ionization in bulk semiconductors.

Phonon-Induced Suppression of Bloch Oscillations in Semiconductor Superlattices: a Monte Carlo Investigation - Meier, Torsten; Rossi, F.; Thomas, P.; Koch, S.W.; Selbmann , P.E.; Molinari, E. (Hot Carriers in Semiconductors)
The progress in the generation of ultrashort laser pulses, together with the development of spectroscopies on this time-scale, has led to a series of experiments which give new insight into the microscopic carrier dynamics in semiconductors. In particular, the energy relaxation of photoexcited carriers has been widely investigated. At the same time, recent progress in the fabrication and characterization of semiconductor heterostructures and superlattices allows a detailed study of a new class of phenomena induced by an applied electric field, such as Bloch oscillations1,2. Both classes of phenomena typically occur on a pico- or femtosecond time-scale, where the coupling between coherent and incoherent phenomena is known to play a dominant role3. Therefore, an adequate theoretical model of the ultrafast dynamics on this time-scale must account for both coherent and incoherent effects on the same kinetic level.

Die Revolution, der Schrecken und das Neue. Konzepte von Legitimität und historischer Gewalt in deutschen Revolutionsdramen um 1800 - Eke, Norbert Otto (Literatur und Erfahrungswandel 1789-1830. Beiträge des 2. Internationalen Corvey-Symposions 8.-12. Juni 1993 in Paderborn)

Parallel Algorithmic Techniques: PRAM Algorithms and PRAM Simulations - Czumaj, Artur

Eine Bibliothek von Basisdiensten für Parallelrechner: Routing, Synchronisation, gemeinsamer Speicher - Wachsmann, Alf

Existenzgründung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis - Unternehmensführung 1)

Existenzgründung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis - Unternehmensführung 1)

Admissible symmetry increasing bifurcations - Dellnitz, M; Heinrich, C (Nonlinearity)